Advances in Psychological and Social Aetiology of Patients with Diabetes - Liu, Xianyuan (Diabetes, metabolic syndrome and obesity, 2023)
Diabetes is a metabolic disease that is affected by internal and external factors. Its prevalence is rising, and it is characterized by a continuous increase in blood glucose levels. With the deepening understanding of diabetes, it is not only necessary to explore its physiological basis, but also to explore the complex interaction between social and psychological factors. In addition to traditional risk factors, the article also highlights the psychological and social aspects of the patient 's impact on the development of diabetes. Because diabetes is not only the result of metabolic imbalances, but also the product of broader background factors, the importance of psychosocial interventions is particularly important. By examining psychosocial dimensions, this review aims to provide a comprehensive understanding of the causes of diabetes. It deeply studies the complex relationship between psychosocial factors and diabetes, and recognizes the complexity of this metabolic disorder. In addition, the article discussed interventions designed to address the psychosocial problems of diabetes, emphasizing the need to take a holistic approach to care for patients. This review explores the impact of psychological and social factors on the incidence, progression and outcome of diabetes, complementing traditional considerations such as obesity, genetic and physiological factors. Recognizing the multifaceted nature of diabetes, this article uses a social etiology perspective to emphasize the important role of social psychological factors. In the process, it has contributed to the ongoing discussion on diabetes management by incorporating a broader social context into the understanding and treatment of this general health problem.